농업인력육성사업의 경제적 수익 효과 : 후계농업경영인육성사업을 중심으로 - 김강호 (한국농촌경제연구원, 2011)
This paper analyzed the economic outcomes resulted from new farmer development program. In order to estimate national economic contribution of the program, polynomial distributed lag model was employed using total factor productivity(TFP) and program budget since starting-point of the program. The results of this study showed that new farmer development program had significantly increased agricultural TFP growth. The elasticity of agricultural TFP with respect to the program is 0.11, which was interpreted as an increase of 0.11% in TFP growth by an 1% increased in the program expenditure. The lagged impacts of the program on TFP began at the sixth year and increased to reach a maximum in the seventh and eighth years. Meanwhile, a marginal internal rate of return was 24.72% per year, which means the program was shown to be a economic profitable investment in Korean agriculture.
Keywords: 후계농업경영인; 경제적 수익; 다항시차분포모형; new farmer; economic return; polynomial distributed lag model